Study of Psychologycal Factor (The Motivation) Relates to The Ability of Associate Nurse to Records The Nursing Care Process in Inpatient Ward - Dewi Murni (Elevate, 2018)
Background: The documentation is everything that is written or printed which relies on as evidence for the authorities. Effective documentation ensures continuity of service, saves time, and minimizes the risk of errors. The implementing of nurse’s documentation is the one way of knowing, monitoring, and concluding for a nursing care process service which are managed by the hospital. Based on those data, it shows the nursing care process in this hospital (49.5%) is lower than the hospital regulation (65%) and Indonesia Health Department (80%). The performance by nurse in implementing nursing care is influenced by organizational factors. Purpose: To look at the factors associated with the performance of nurses in the implementation of nursing care in hospitals. Method: This study uses cross-sectional design. Population and samples in this study were nurses in hospitals with sample as many as 89 people, with simple random sampling. Instrument that was used is questionnaires. Result: Test results of the bivariate chi-square statistic indicates that there is no significant Psychological Factors (Motivation) (p = 0.095. Conclusion: Results of this study recommend to the Director of Hospitals to motivate and provide reward the nurses